The factors that Influence Earning Response Coefficient: In the Context of Indonesian Capital Market in Year 2015-2018 - Vincent Aurelio Benny; Dadang Muljawan; Herbert Hasudungan (ProBisnis : Jurnal Manajemen, 2023)
Investing in a business that consistently generates profits is what every investor undoubtedly wants to do. Investors want to put their money into profitable businesses, without a doubt. The effective application of operations management and financial regulations has led to these high-quality results. When building an investment portfolio, investors should be far more knowledgeable of and devote attention to the quality of profits and internal control of the firm. With Corporate Governance serving as the moderation variable and earning response coefficient serving as the dependent variable, this empirical study aims to determine the relationship between Conservatism, which is a way of presenting numbers in financial statements, return on assets, asset turnover, and Ectivity Performance. In this study, manufacturing companies in the basic and chemical industries that have been registered on the National Stock Exchange of india (IDX) between 2015 and 2018 were examined using purposeful selection and panel data regression analysis. The main conclusions of this study were that asset turnover, return on assets, and Conservatism all significantly affect the earning response coefficient. Additionally, it was shown that the earning response coefficient is influenced by earnings quality, which is tempered by Corporate Governance.